THE USE OF NOMINALIZATION IN EMI STUDENT WRITING - A LONGITUDINAL PERSPECTIVE - Thanh Ha, Do Thi; Thuy Linh, Nguyen Thi (VNU Journal of Foreign Studies; Vol 35 No 3, 2019)
ESL student writing development has been a concern in second language research. However, most of the current studies focus on the development in the language teaching context.  The context of English as a medium of instruction (EMI) has been under-represented, in which how EMI students’ writing changes over time without teaching or explicit feedback on language has not been well-researched. This paper aimed at tracing the development of students writing in an EMI program in Vietnam. Particularly, the paper analyzed one particular aspect of syntactic complexity (i.e. nominalization), a construct considered important in developmental profiling of individuals (Lu, 2011; Vyatkina, 2013).  Assignments from three EMI students were collected over three semesters and changes in their use of nominalization were closely investigated and developmental patterns were described. The results of the study inform ESL and SLA researchers and academics of how academic writing develops in a non-instructed environment and accordingly enable EMI program coordinators and designers to provide appropriate language supports to students during the course.